(untitled) (Scientific journal of the Fergana State University, 2025)
This article is dedicated to the issues of developing strength and physical qualities of primary school students. The research provides an in-depth analysis of children’s age-specific physical development characteristics, methodology for forming strength qualities, and pedagogical approaches.